Epistemological Perspective on Mathematical Thinking Patterns of Lower-Grade Elementary Students - Pangestika, Rintis Rizkia; Ratnaningsih, Arum; Nurhidayati, Nurhidayati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the mathematical thinking patterns of lower-grade elementary school students in solving numeracy problems from an epistemological perspective. The study employed a qualitative case study approach involving six third-grade students at SDN Purworejo, selected purposively based on variations in numeracy ability. Data were obtained from students’ numeracy problem-solving tasks, classroom observations, and semi-structured interviews, while secondary data were taken from school documents such as lesson plans and assessment records. The collected data were analyzed using thematic analysis following the Miles, Huberman, and Saldaña (2020) framework, consisting of data reduction, data display, and conclusion drawing. The results revealed three general patterns of mathematical thinking among students: intuitive, procedural, and emerging logical thinking. These findings indicate that most lower-grade students still rely on intuitive and procedural approaches, highlighting the need for learning strategies that promote conceptual understanding, multiple representations, and teacher scaffolding to strengthen early numeracy skills